1974
DOI: 10.1104/pp.53.6.879
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light on the Tricarboxylic Acid Cycle in Green Leaves

Abstract: Excised green leaves of mung bean (Phaseolus aureus L. var. Mungo) were used to determine the effect of light on the rate of endogenous respiration via the tricarboxylic acid cycle. ILlumination with white light at an intensity of 0.043 gram calories cm'minn (approximately 8600 lux) of visible radiation (400-700 nm) gave a rate of apparent photosynthesis, measured as net C02 uptake, of 21 mg CO2 dm-2hr-' which was about 11-fold greater than the rate of dark respiration. The feeding of '4CO2 or 14C-labeled acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
3
9
0
Order By: Relevance
“…In these, the sum of aspartate and malate is plotted for simplicity. Figure 2a shows that in A. hastata, little radioactivity was transferred to sucrose on illumination, a response consistent with that in mung beans (6). The net loss of label from the malate + aspartate in the light reappeared in glutamate.…”
Section: Methodssupporting
confidence: 51%
See 3 more Smart Citations
“…In these, the sum of aspartate and malate is plotted for simplicity. Figure 2a shows that in A. hastata, little radioactivity was transferred to sucrose on illumination, a response consistent with that in mung beans (6). The net loss of label from the malate + aspartate in the light reappeared in glutamate.…”
Section: Methodssupporting
confidence: 51%
“…In leaves of higher plants, this conclusion is supported by studies with labeled tricarboxylic acid cycle intermediates (6,7), and by the persistence in the light of 02 uptake at low concentrations of 0°known to inhibit glycolate synthesis and metabolism, or photorespiration (25,30). The role of continued tricarboxylic acid cycle respiration in the light in green cells is not clearly understood but it contributes to C02-generating reactions in these tissues (23,30).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In the previous paper (9) evidence was presented which indicated that a relatively high light intensity had only a temporary effect in depressing the rate of the tricarboxylic acid cycle in detached green leaves of mung bean (Phaseolus aureus L. var. Mungo).…”
mentioning
confidence: 99%